Divide and rule» by means of language (for example the newspaper «Chervonyi hіrnyk») (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article refers to abidance by professional and ethical standards of the regional representatives of the printed media. Texts that contain verbal aggression, promote intolerance, impose confrontation, exploit the idea of «circle of friends», have discriminating tone are analyzed. The author exacts faithful information, its impersonal presentation, ethical reflections of journalist. The recommendations regarding the removal of the information tension in times of crisis are suggested.
Keywords: media; information product; text; the ethical principles of journalism